Prevalence of type of dental caries among the patients visiting a tertiary health care center in the Western region of Nepal - Pradhan, Babita; Kunwar, Deepa; Ranjit, Rebicca; Gyawali, Namrata (Journal of Gandaki Medical College-Nepal, 2024)
Introduction: Dental caries is one of the major public health problems globally due to its high prevalence and significant social impact. The objective of the present study was to assess the most prevalent type of dental caries among the studied population. Methods: This cross-sectional study was conducted among 300 participants. The data were collected by intraoral examination of the subjects, where the type of dental caries in each patient was examined. The surfaces infected with dental caries were recorded as occlusal pit and fissure caries, root caries, smooth surface caries, and recurrent caries. Descriptive statistical methods were applied for data analysis. Results: The most prevalent type of dental caries was found to be the occlusal pit and fissure caries 595(66.04%) followed by smooth surface caries 220(24.42%), recurrent caries 54(5.99%) and root caries 32(3.55%). The occlusal pit and fissure caries was more prevalent in the mandibular arch 298(67.73%). Males had more prevalence of different types of dental caries. Based on the age group, 40 to 50 years age group had the most prevalent type of occlusal pit and fissure caries 60(20%). Conclusions: The results showed a high prevalence of occlusal pit and fissure caries in the study population followed by smooth surface caries, recurrent caries, and root caries.